2010
DOI: 10.1007/s11999-009-1086-1
|View full text |Cite
|
Sign up to set email alerts
|

Leg Length and Offset Measures with a Pinless Femoral Reference Array during THA

Abstract: The bony fixation of reference marker arrays used for computer-assisted navigation during total hip arthroplasty (THA) theoretically involves the risk of fracture, infection, and/or pin loosening. We asked whether intraoperative assessment of leg length (LL) and offset (OS) changes would be accurate using a novel pinless femoral reference system in conjunction with an imageless measurement algorithm based on specific realignment of the relationship between a dynamic femoral and pelvis reference array. LL/OS me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
1
19
4
Order By: Relevance
“…As for the effect of this difference in the reference on anteversion measurement, Turley et al assessed the validity of the measurement principle employed in the navigation system and concluded that the navigation results can be reasonably compared to the values measured on CT images [ 15 ]. There have been several studies examining leg length change after THA with image-free navigation [ 16 - 18 , 19 ]. Previous study examined the accuracy of leg length adjustment in THA using a previous version of image-free navigation in which the leg length was intraoperatively measured without a femoral clamp attached to the femur.…”
Section: Discussionmentioning
confidence: 99%
“…As for the effect of this difference in the reference on anteversion measurement, Turley et al assessed the validity of the measurement principle employed in the navigation system and concluded that the navigation results can be reasonably compared to the values measured on CT images [ 15 ]. There have been several studies examining leg length change after THA with image-free navigation [ 16 - 18 , 19 ]. Previous study examined the accuracy of leg length adjustment in THA using a previous version of image-free navigation in which the leg length was intraoperatively measured without a femoral clamp attached to the femur.…”
Section: Discussionmentioning
confidence: 99%
“…The surgeon may control the limb length and achieve an accurate restoration of leg length and joint offset [20, 3133]. …”
Section: Navigation For Orthopedic Surgerymentioning
confidence: 99%
“…This technique also harbours the possibility of controlling leg length and offset changes during THA [ 14 ]. To reduce the risk of pin infection and fractures due to the bony fixation of reference markers [ 15 ], novel pinless navigation devices have been developed for achieving appropriate LL and OS values [ 16 ]. However, direct translatory and rotational variations between the pinless array and the femoral bone up to 8 mm in translation and 9° in rotation are associated with the risk of potential error during measurements [ 17 ].…”
Section: Introductionmentioning
confidence: 99%